Study of regional topography and rainfall distribution using the Inverse Distance Weighted (IDW) interpolation method in Serang City - Al Kansaa, Hanifah Nuraini; Ruhiat, Yayat; Saefullah, Asep (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
Indonesia has a reasonably large area with a high level of weather and climate diversity, causing various parts of the region to experience rain with different characteristics, one of which is influenced by the topography of the area so that it is not possible to use just one rain gauge to describe the rain in a region. Therefore, it requires the average rainfall from several nearby rain measurement stations or posts. This research aims to describe the influence of regional topography on the distribution of rainfall in Serang City using the Inverse Distance Weighted (IDW) interpolation method by varying the power value and processing and analyzing using the Geographic Information System (GIS). The research method used is non-experimental quantitative with spatial reclassification analysis. The data used is secondary data collected from previously existing data. The results of the research show that in areas that are at low altitudes and have gentle slopes, the average rainfall will be low, namely 1414.91 mm/year, and vice versa; if areas are at high altitudes and have steep slopes, the average rainfall is The rainfall will be high namely 1644.6 mm/year.